A Comparative Study of Intramedullary Interlocking Nailing Versus Distal Tibial Plating in Distal Tibial Fractures (The Insight, 2026)
Background: Distal tibial fractures are difficult to manage because of limited soft tissue coverage and a high risk of complications. Intramedullary interlocking nailing (IMIL) and distal tibial plating (DTP) are commonly used fixation methods; however, the optimal technique remains controversial. This study aimed to compare the clinical and functional outcomes of IMIL and DTP in the management of distal tibial fractures. Methods & Materials: This comparative study was conducted in the Department of Orthopedics, Shaheed Ziaur Rahman Medical College Hospital, Bogura, Bangladesh, from July to December 2025. Fifty patients with distal tibial fractures were equally allocated into two groups: IMIL (n=25) and DTP (n=25). Socio-demographic variables, fracture characteristics, operative parameters, time to union, functional outcomes (Johner and Wruhs criteria), and complications were recorded and analyzed. Results: Baseline characteristics were comparable between groups. IMIL showed significantly shorter operative time (68.4 vs 92.6 minutes), lower blood loss (120 vs 210 ml), shorter hospital stay (4.1 vs 6.3 days), and earlier partial weight bearing (4.5 vs 6.2 weeks) (p